The Eichmann trial reconsidered - Wittmann, Rebecca, 1970- (German and European studies., 2021)
"The Eichmann Trial Reconsidered brings together leading authorities in a transnational, international, and supranational study of Adolf Eichmann, who was captured by the Israelis in Argentina and tried in Jerusalem in 1961. The essays in this important new collection span the disciplines of history, film studies, political science, sociology, psychology, and law. Contributing scholars adopt a wide historical lens, pushing outwards in time and space to examine the historical and legal influence that Adolf Eichmann and his trial held for Israel, West Germany, and the Middle East. In addition to taking up the question of what drove Eichmann, contributors explore the motivation of prosecutors, lawyers, diplomats, and neighbouring countries before, during, and after the trial ended. The Eichmann Trial Reconsidered puts Eichmann at the centre of an exploration of German versus Israeli jurisprudence, national Israeli identities and politics, and the conflict between German, Israeli, and Arab states."--